GALVANIC CORROSION OF ZINC ANODE AND COPPER CATHODE CELL - Çek, Nurettin (My University, 2018)
Detection and control of galvanic corrosion is a critical aspect of engineering for the chemical processes used in the fabrication of metals, alloys and materials industry. Galvanic corrosion can occur when two metals having different status in the electrochemical ambient are configured in mutual interaction within the galvanic cell structure and are exposed to the ion conducting electrolyte. In this study, ion-containing water was used as an electrolyte, the zinc as the anode electrode, copper as the cathode was used as an electrode, and a galvanic cell was fabricated. The formation of corrosion products with time on zinc anode reduced the voltage and current in galvanic cell considerable and anode film layer of considerable increase. Time-dependent experiments have provided good sources of information about the performance of the zinc anode electrode and the copper cathode electrode in the galvanic cell.
Keywords: Mühendislik; Kimya